Analysis Of Factors Influencing Patient Safety Incidents at Royal Prima Medan General Hospital in 2021 - Rizka Rahmadana; Rafael Ginting; Sri Lestari Nasution; Ermi Girsang (International Journal of Health and Pharmaceutical (IJHP), 2024)
Incident safety patients must be minimized to avoid undesirable danger during maintenance in the hospital. Perception of health workers reporting patient safety incidents at the Royal Prima Medan General Hospital still needs to be higher. Low perception of health workers in writing incident Patient safety is related to individual and organizational factors. The study aims to identify the influence factor on patients' personal and corporate incident safety in the inpatient room of royal prima hospital medan. The type of research used is a method survey with a cross-sectional approach. The population in the study of health workers at the Royal Prima General Hospital in Medan was 259 people, and the sample was 119. Collection data with primary, secondary, and tertiary data was analyzed with multiple logistic regression statistical tests with a level of trust of 95%. Results study show bring individual factors (knowledge with p-value = 0.021 and experience with p-value=0.021) effect-on-patient safety incident reporting and organizational factors (organizational environment with p-value = 0.038 and power with p-value=0.014) effect on reporting incident safety patient, individual characteristics (motivation with p-value = 0.557) have no impact on writing incident safety patient And factor organization (organizational culture with p-value =0.535) has no effect to reporting incident patient safety and most influence reporting incident patient safety in Royal Prima General Hospital Medan is a knowledge variable (OR=155.6). They are recommended for a hospital for-develop system information integration related to writing incident patient safety and officer health to increase the perception of officer health through improvement, knowledge, and experience of officer health.